Effect of machining parameters on surface quality of w-edmed Ti6Al4V alloy in ultrasonic assisted magnetic abrasive finishing technique - Celik, Mahmut; Gurun, Hakan; Caydas, Ulan; Koklu, Ugur (Gazi Univ, Fac Engineering Architecture, 2023)
Graphical/Tabular In this study, a CNC milling machine was modified to include an ultrasonic system to finish Wire-EDMed Ti6Al4V alloy with Ultrasonic assisted magnetic abrasive finishing and the effects of machining parameters on surface quality and MRR were investigated. As seen in Figure A, improvements up to 90% occurred in surface roughness values. On the other hand, it was determined that ultrasonic support contributed 58% and 15%, respectively, in terms of surface quality and MRR. Figure A. (a) Experimental setup (b) Surface topologies of the specimens before/after MAF and UDMAF processPurpose: The EDM method is frequently used in the machining of difficult-to-cut metals such as titanium alloys. As a result of the EDM method, unwanted formations such as recast layer, micro cracks and craters occur on the workpiece surface. These formations negatively affect the surface quality. In order to improve the surface quality of EDMed surfaces, a secondary finishing process is required. Magnetic abrasive finishing method is a method that can be used for this purpose. In this study, it is aimed to increase the surface quality of Wire-EDMed Ti6Al4V alloy with Ultrasonic assisted MAF method.Theory and Methods: In MAF technique, iron-based powders and abrasives are used together. These abrasives form a flexible magnetic brush assembly with iron powders along the magnetic field lines generated by the magnetic poles. The brush acts as a multi-point cutter. In this study, Wire -EDMed Ti6AL4V plates' surface quality was improved by ultrasonic assisted magnetic abrasive finishing method The experiments were carried out under the experimental conditions determined in the accordance of previous studies by CNC milling machine and improvement ratios of surface quality and material removal rates (MRR) were measured.Results: As a result of the experiments, an average improvement of 36 % and 57 % was observed in the Ra for MAF and UDMAF respectively. This improvement was found to be up to 81 % and 90 % in the appropriate experimental conditions. Additionally, MRR ratio was measured as 4.95 mg/min and 5.74 mg/min on average for MAF and UDMAF respectively.Conclusion: As a conclusion, MAF is a suitable method for improvement of surface quality of w-EDMed Ti6Al4V alloy. On the other hand, ultrasonic assist increased the efficiency of the method.
Ultrasonik destekli manyetik aşındırıcılarla işleme yönteminde işleme parametrelerinin tel erozyon ile işlenmiş Ti6Al4V alaşımının yüzey kalitesi üzerindeki etkileri
Keywords: Wire-EDM; Ultrasonic assisted MAF; Surface quality; Ti6Al4V; Material removal rate